Encyclopedia Brown and the case of the slippery salamander - Sobol, Donald J., 1924-; Chang, Warren (New York, N.Y. : Yearling/Random House, 2003)
Encyclopedia Brown, the super sleuth in sneakers, solves ten new mysteries, including The case of the slippery salamander, The case of the banana burglar, and The case of the dead cockroach.
"#22"--Jacket cover.
Keywords: Mystery and detective stories; Literary recreations